Enhancing Public Service Quality in Medan City through E-Government Initiatives: The Role of Acceptability and Work Efficiency - Vera Asihna Riris Pasaribu; Jonson Rajagukguk; Sunday Ade Sitorus (ARRUS Journal of Social Sciences and Humanities, 2026)
This study aims to examine the effect of acceptability and work efficiency on public service quality through E-Government initiatives in Medan City. The study was motivated by the need to improve public service delivery through digital governance, particularly in local government contexts where public acceptance, administrative efficiency, and digital service initiatives play an important role in strengthening service performance. This research employed a descriptive quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The population consisted of 2,494,512 residents of Medan City in 2023, and the sample was determined using the Slovin formula with a 10% margin of error, resulting in 100 respondents selected through accidental sampling.The results indicate that acceptability has a significant effect on the improvement of public service quality in Medan City. Work efficiency also significantly contributes to improving public service quality. Furthermore, acceptability and work efficiency significantly influence E-Government initiatives. The findings also show that E-Government initiatives significantly contribute to the improvement of public service quality. In addition, E-Government initiatives serve as an intervening variable in the relationship between acceptability and public service quality, as well as between work efficiency and public service quality. These findings confirm that public service improvement is not only determined by the availability of digital government systems, but also by the extent to which such systems are accepted by citizens and supported by efficient work processes within government institutions.This study concludes that acceptability, work efficiency, and E-Government initiatives are important determinants of public service quality improvement in Medan City. The higher the public acceptability of E-Government technology and the more efficient the work processes implemented by public institutions, the stronger the contribution of E-Government initiatives to improving public service quality. Therefore, the Medan City Government needs to continuously strengthen citizen-oriented E-Government initiatives to create public services that are more efficient, responsive, transparent, and aligned with citizens’ needs